Lavandula stoechas essential oil from Morocco as novel source of antileishmanial, antibacterial and antioxidant activities. (October 2017) - Bouyahya, Abdelhakim; Et-Touys, Abdeslam; Abrini, Jamal; Talbaoui, Ahmed; Fellah, Hajiba; Bakri, Youssef; Dakka, Nadia
Abstract: This study aimed to reveal the chemical composition of Lavandula stoechas L. ( L . stoechas ) essential oils and to evaluate their antileishmanial, antibacterial and antioxidant properties. The essential oil was extracted by hydrodistillation using Clevenger apparatus. The chemical composition of L. stoechas essential oil was determined using GC-MS analysis. The antibacterial activity was tested against pathogenic strains using the diffusion method, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) by microtitration assay. The antioxidant activity was estimated by DPPH free radical scavenging ability and ferric-reducing power. The antiparasitic activity was tested against Leishmania major, Leishmania tropica and Leishmania infantum using MTT (3-(4.5-dimethylthiazol-2yl)−2.5-diphenyltetrazolium bromide) assay. The major components of L . stoechas essential oils are represented by fenchone (31.81%), camphor (29.60%), terpineol (13.14%), menthone (8.96%) and eucalyptol (5.88%). The oil has revealed an important antioxidant capacity compared with ascorbic acid and Trolox. The highest inhibition was obtained against Listeria monocytogenes and Staphylococcus aureus MBLA by a diameter inhibition of 23 ± 0.85 and 21 ± 0.25 mm respectively. The lowest MIC and MBC values were obtained against L . monocytogenes (MIC=MBC=0.25% (v/v)). The essential oil was most active against L . major with an IC50 value of 0.9 ± 0.45% (v/v). From these results, we conclude that L . stoechas essential oils could have potential applications in the food and pharmaceutical industries. Highlights: The chemical composition and biological activities of Lavandula stoechas essential oil were investigated. The essential oil of Lavandula stoechas contains the fenchone, the camphor and the terpineol as main compounds. Lavandula stoechas essential oil showed interesting antiradical capacities. Lavandula stoechas essential oil had a remarkable bactericidal action against tested bacteria. This study is the first that investigate the antileishmanial activity of Lavandula stoechas essential oil, and showed an important leishmanicidal effect against Leishmania major and Leishmania infantum.